2007
DOI: 10.2500/aap.2007.28.3062
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive report of the efficacy, safety, quality of life, and work impact of Olopatadine 0.6% and Olopatadine 0.4% treatment in patients with seasonal allergic rhinitis

Abstract: Seasonal allergic rhinitis (SAR) treatment should reduce symptoms and help patients resume normal function. This study was performed to determine the effect of olopatadine (Olo) nasal spray on symptoms, quality of life (QoL), work, and activities of SAR patients. A pooled analysis was conducted of two Institutional Review Board-approved, randomized, double-blind clinical trials that compared 2-week treatment with Olo 0.6% and Olo 0.4% to placebo. Symptoms were assessed with the Total Nasal Symptom Score (TNSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
1
22
1
Order By: Relevance
“…percentage of impairment while working) and total activity impairment (TAI) other than work due to AD during the previous week can be evaluated. The impact of allergic diseases such as allergic rhinitis on work productivity and activity using WPAI allergy‐specific (WPAI‐AS) has been assessed . In addition, the impact of certain skin diseases such as chronic spontaneous urticaria, chronic hand dermatitis and psoriasis using WPAI has been evaluated in Western countries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…percentage of impairment while working) and total activity impairment (TAI) other than work due to AD during the previous week can be evaluated. The impact of allergic diseases such as allergic rhinitis on work productivity and activity using WPAI allergy‐specific (WPAI‐AS) has been assessed . In addition, the impact of certain skin diseases such as chronic spontaneous urticaria, chronic hand dermatitis and psoriasis using WPAI has been evaluated in Western countries .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of allergic diseases such as allergic rhinitis on work productivity and activity using WPAI allergyspecific (WPAI-AS) has been assessed. 3,4 In addition, the impact of certain skin diseases such as chronic spontaneous urticaria, chronic hand dermatitis and psoriasis using WPAI has been evaluated in Western countries. [5][6][7] Murota et al 8,9 also determined the impact of antihistamines on the impaired productivity of patients with pruritic skin diseases including eczema/dermatitis, urticaria, AD, pruritus cutanea, prurigo and psoriasis using the WPAI-AS in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…These results are comparable with two additional studies in older children (Ͼ12 years of age) and adults that showed significant improvements in quality-of-life outcomes for subjects suffering from seasonal SAR who used OLO. 18,19 Although the study was not designed to examine differences between the two active dosing regimens, the efficacy outcomes in each of the active dosing groups suggest that, whereas both regimens provide efficacy, there is no benefit achieved from increased dosing.…”
Section: Discussionmentioning
confidence: 97%
“…2 Fortunately, the past decades have afforded tremendous insights into the pathophysiology and mechanisms of allergic rhinoconjunctivitis, 1 leading to diverse and effective treatment strategies, ranging from antihistamines to specific immunotherapy. 3,4 Consequently, the use of first-and second-generation antihistamines has become the standard of therapy for symptom management, but their ability to impede the wheal and flare responses to allergen skin testing makes the diagnosis of allergic rhinoconjunctivitis especially challenging in those individuals who regularly use histamine-antagonizing medications. For example, the oral administration of astemizole, 5,6 azelastine, 5 cetirizine, 5,7-9 chlorpheniramine, 10,11 diphenhydramine, 11 doxepin, 12 fexofenadine, 13 and loratidine, 5,8,9,13 among others, has been documented to suppress the wheal and flare response during allergy skin tests.…”
mentioning
confidence: 99%
“…[1][2][3][4] Such a prevalent disease contributes greatly to diminished quality of life as well as to enormous economic costs, both direct and indirect. 2 Fortunately, the past decades have afforded tremendous insights into the pathophysiology and mechanisms of allergic rhinoconjunctivitis, 1 leading to diverse and effective treatment strategies, ranging from antihistamines to specific immunotherapy.…”
mentioning
confidence: 99%